2015
DOI: 10.1016/j.cub.2015.08.034
|View full text |Cite
|
Sign up to set email alerts
|

Passive Transport Disrupts Grid Signals in the Parahippocampal Cortex

Abstract: Summary Navigation is usually thought of relative to landmarks, but neural signals representing space also use information generated by an animal’s movements. These signals include grid cells, which fire at multiple locations forming a repeating grid pattern. Grid cell generation depends upon theta rhythm, a 6-10 Hz EEG oscillation that is modulated by the animals’ movement velocity. We passively moved rats in a clear cart to eliminate motor related self-movement cues that drive moment-to-moment changes in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
96
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(103 citation statements)
references
References 37 publications
7
96
0
Order By: Relevance
“…What underlying principles govern this cue-integration process? Previous work has shown that grid cells rely on both self-motion input 10 , which can reflect locomotion and optic flow cues, as well as an error correcting signal provided by environmental landmarks 12 . However, gain changes alter the relationship between distance traveled and the locations of known landmarks, as well as the relationship between locomotion and optic flow.…”
Section: Resultsmentioning
confidence: 99%
“…What underlying principles govern this cue-integration process? Previous work has shown that grid cells rely on both self-motion input 10 , which can reflect locomotion and optic flow cues, as well as an error correcting signal provided by environmental landmarks 12 . However, gain changes alter the relationship between distance traveled and the locations of known landmarks, as well as the relationship between locomotion and optic flow.…”
Section: Resultsmentioning
confidence: 99%
“…For mEC recordings, classification has previously been performed by first calculating descriptive values for each cell class (grid score, border score, spatial information, HD mean resultant length) and by then comparing the values to those calculated from the shuffled data of all recorded mEC cells pooled together (Figure S2A) (Barry et al, 2012; Bjerknes et al, 2015; Boccara et al, 2010; Koenig et al, 2011; Kropff et al, 2015; Krupic et al, 2015; Langston et al, 2010; Latuske et al, 2015; Perez-Escobar et al, 2016; Stensola et al, 2012; Tang et al, 2014; Wills et al, 2010; Winter et al, 2015; Zhang et al, 2013). However, pooling shuffled data across all cells fails to account for the firing statistics of individual cells, most notably the relationship between a cell’s firing rate and its spatial information (Figure S2B) (Rolls et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…His thinking on hippocampal-cortical interactions in memory organization and control is beautifully summarized in his 2017 Annual Review of Psychology article 47 . intrinsic MEC dynamics but also how external inputs from the hippocampus 242 , the medial septum 181,182 , and locomotor [204][205][206][207]262 and head direction circuits 263 contribute to the emergence of grid patterns (Box 1).…”
Section: In Memoriammentioning
confidence: 99%